Ocimum basilicum (Basil) Modulates Apoptosis and Neurogenesis in Olfactory Pulp of Mice Exposed to Chronic Unpredictable Mild Stress - Ayuob, Nasra N.; Balgoon, Maha J.; Ali, Soad; Alnoury, Ibrahim S.; ALmohaimeed, Hailah M.; AbdElfattah, Amany A. (Frontiers in Psychiatry, 2020)
Background Ocimum basilicum(O. basilicum) was described to have antidepressant and anxiolytic activities. Although the relationship between the main olfactory bulb (MOB) and depression was recently reported, the chronic stress-induced dysfunction of the MOB is not clearly described. Objectives This study aimed to assess the efficacy of inhalation of O. basilicum essential oils in improving chronic unpredictable mild stress (CUMS)-induced changes in MOB of mice and understand the mechanism underlying such effect. Materials and Methods Adult male mice (n=40) were assigned into four groups included the control, CUMS-exposed, CUMS + fluoxetine (FLU), CUMS + O. basilicum. Behavioral changes, serum corticosterone level, and gene expression of GFAP, Ki 67, and caspase-3 were assessed using real-time PCR (RT-PCR). Histopathological and immunochemical examination of the MOB was performed. Results FLU and O. basilicum significantly down-regulated (p = 0.002, p<0.001) caspase-3 gene expression indicating reduced apoptosis and up-regulated (p = 0.002, p < 0.001) Ki67 gene expression indicating enhanced neurogenesis in MOB, respectively. FLU and O. basilicum-treated mice markedly improved MOB mitral cell layer distortion and shrinkage induced by CUMS. Conclusion O. basilicum relieved both biochemically and histopathological chronic stress-induced changes in the main olfactory bulb possibly through up-regulation of gene expression of GFAP and Ki67 and down-regulation of caspase-3 in the MOB.